On two new deep-sea species of the genus Campylaspis G. O. Sars, 1865 (Cumacea: Nannastacidae) from Brazil - Duda, Maria Luiza De F.; Roccatagliata, Daniel; Lucatelli, Debora; Filho, Jesser F. Souza- (Zootaxa, 2025)
Currently, 15 species of the genus Campylaspis, collected between 40 and 4,680 m depth, are known from Brazil. In the present study, two additional species collected from Campos Basin, Rio de Janeiro and Espírito Santo States, between 393 and 733 m depth, are described. An updated list of all the Campylaspis species reported from Brazil along with an identification key for the deep-sea species are presented.